One Hundred Short Problems in Corporation Finance (Book). - Hubbard, Joseph B. (The Accounting Review, 1937)
Reviews the book "One Hundred Short Problems, in Corporation Finance," by Herbert E. Dougal and Ernst A. Dauer.